Lithium manganese iron phosphate positive electrode material and preparation method thereof

By using a carbon source after reacting nanosilver/thioglycol-epoxy composite solution with an aminocarbon nanotube, the resistance of lithium manganese iron phosphate positive electrode material in the prior art is solved. The problem of high rate significantly improves the conductivity and electrochemical properties of the material.

CN119495732APending Publication Date: 2025-02-21HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411694900.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-21

Smart Images

  • Figure BDA0005151866080000101
    Figure BDA0005151866080000101
Patent Text Reader

Abstract

The invention discloses a lithium manganese iron phosphate positive electrode material and a preparation method thereof, and belongs to the technical field of lithium batteries, the preparation method of the lithium manganese iron phosphate positive electrode material comprises the following steps: dissolving a soluble iron source, a soluble manganese source and a complexing agent in 100 mL of deionized water, adjusting the pH value of the mixed solution to 2-4, and heating and stirring for 2-6 h to obtain xerogel; calcining the dry gel, taking out, cooling and grinding to obtain powder A; calcining the powder A in a nitrogen atmosphere, and grinding to obtain powder B; uniformly mixing the powder B, a lithium source, a phosphorus source, a carbon source and 70mL of deionized water, sanding, and spray-drying slurry after sanding to obtain powder C; and calcining the powder C in a nitrogen atmosphere, crushing, and sieving to obtain the lithium iron manganese phosphate positive electrode material. The lithium manganese iron phosphate positive electrode material prepared by the method has excellent conductivity and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a lithium manganese iron phosphate positive electrode material and a preparation method thereof. Background Art

[0002] Lithium iron phosphate cathode materials have occupied a certain market in the fields of energy storage and power due to their advantages of low cost, good cycle performance and safety performance. At present, the preparation methods of lithium iron phosphate composite materials are gradually converging, and the differences in various performance indicators are getting smaller and smaller, but they cannot meet the market demand for high cost-effective cathode materials for lithium-ion batteries.

[0003] Lithium manganese iron phosphate is derived from lithium iron phosphate, maintaining the original cost and safety advantages and achieving one of the breakthrough paths to improve performance. The theoretical capacity of lithium manganese iron phosphate is 170mAh / g, just like lithium iron phosphate, but its electrode potential (4.1V) is higher than that of lithium iron phosphate, and it has a wider application prospect. The introduction of manganese makes it difficult for material particles to grow, limiting the development of high compaction density lithium manganese iron phosphate materials; in addition, the side reactions between manganese-based materials and electrolytes are intensified, and the dissolution of manganese deteriorates the life of the battery cell. Therefore, to achieve the large-scale application of lithium manganese iron phosphate materials in high-energy density batteries, it is necessary to improve the material stability, compaction density and other aspects.

[0004] The prior art usually uses carbon wrapping to improve the performance of lithium iron manganese phosphate materials. Carbon wrapping can form a good conductive network through the mutual contact between the carbon layer and the particles, thereby improving the electronic conductivity of the material. The patent with patent publication number CN114620703A discloses a carbon-coated lithium iron manganese phosphate composite material and its preparation method. The patent adds a manganese source to a solvent for particle refinement to obtain a pre-treated slurry, and then mixes it with a lithium source, an iron source, a phosphorus source and a carbon source and then refines the particles to obtain a primary slurry; the primary slurry is dried to obtain a primary precursor particle, and then placed in a nitrogen furnace for a primary sintering to obtain a primary sintered material; the primary sintered material is added to a solvent, a carbon source is added, and wet ball milling is used to obtain a secondary slurry; the secondary slurry is dried to obtain a secondary precursor particle, and then placed in an inert atmosphere for secondary sintering to obtain a secondary sintered material; the secondary sintered material is crushed to obtain a carbon-coated lithium iron manganese phosphate composite material. However, the lithium iron manganese phosphate positive electrode material prepared by the patent and the prior art still has the disadvantage of large resistivity. Summary of the invention

[0005] In order to solve the problem that the lithium iron manganese phosphate positive electrode material prepared by the prior art still has the disadvantage of high resistivity, the object of the present invention is to provide a lithium iron manganese phosphate positive electrode material and a preparation method thereof.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for preparing a lithium manganese iron phosphate positive electrode material comprises the following steps:

[0008] S1: dissolving a soluble iron source, a soluble manganese source and a complexing agent in 100 mL of deionized water, adjusting the pH value of the mixed solution to 2-4, and heating and stirring for 2-6 hours to obtain a dry gel;

[0009] The molar ratio of the soluble iron source (calculated as Fe), the soluble manganese source (calculated as Mn) and the complexing agent is x:y:(0.1-1.0), x+y=1.

[0010] S2: taking out the dry gel after calcination, cooling and grinding to obtain powder A;

[0011] S3: calcining and grinding powder A under a nitrogen atmosphere to obtain powder B;

[0012] First, add the iron source, manganese source and chelating agent. On the one hand, the chelating agent chelates the iron and manganese together to make them evenly distributed. On the other hand, it can act as a carbon source to form a carbon coating on the surface of the iron-manganese precursor after high-temperature calcination, which can prevent the dissolution of manganese ions.

[0013] S4: Powder B, lithium source, phosphorus source, carbon source and 70 mL of deionized water are mixed evenly and then sand-milled. After sand-milling, the slurry is spray-dried to obtain powder C, where the carbon source is obtained by drying after the reaction of nanosilver / thiol-polyethylene glycol-epoxy composite solution with amino carbon nanotubes.

[0014] The molar ratio of powder B (calculated as Fe+Mn), lithium source (calculated as Li) and phosphorus source (calculated as P) is 1:1:1; the mass of carbon source accounts for 4-8% of the total mass of all raw materials except water.

[0015] S5: calcining powder C in a nitrogen atmosphere, and then crushing and sieving to obtain lithium manganese iron phosphate positive electrode material.

[0016] Furthermore, in step S1, the soluble iron source is one or more of ferrous sulfate, ferrous nitrate, ferrous acetate, ferric sulfate, ferric nitrate and ferric acetate; the soluble manganese source is one or more of manganous sulfate, manganous nitrate and manganous acetate; and the chelating agent is one or more of citric acid, ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, sodium gluconate and sodium alginate.

[0017] Further, in step S2, the calcination temperature is 200-400°C, and the calcination time is 1-10min;

[0018] Furthermore, in step S3, the calcination temperature is 400-500° C., and the calcination time is 1-2 h.

[0019] Furthermore, in step S4, the sand grinding particle size D50≤250nm; the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium nitrate and lithium acetate; the phosphorus source is one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate and disodium hydrogen phosphate.

[0020] Furthermore, in step S5, the calcination temperature is 600-800°C, and the calcination time is 8-10h; and the particle size after crushing is D50≤1.3μm.

[0021] Further, the steps of preparing the carbon source are as follows:

[0022] A1: Mix thiol-polyethylene glycol-epoxy with DMF to obtain a mixed solution A, and evenly stir 0.06 mol / L of the mixed solution A, 0.01 mol / L silver nitrate aqueous solution, and 0.5 mol / L sodium borohydride aqueous solution, and react at room temperature for 30-40 minutes to obtain a nanosilver / thiol-polyethylene glycol-epoxy composite solution.

[0023] The volume ratio of the mixed solution A, the silver nitrate aqueous solution and the sodium borohydride aqueous solution is 5:5:1; the amount ratio of the mercapto-polyethylene glycol-epoxy to DMF in the mixed solution A is 6g:100-150mL.

[0024] Silver nitrate ionizes into silver ions in water, and sodium borohydride, as a strong reducing agent, can reduce silver ions to silver atoms, thereby forming nanosilver particles. The thiol groups in the thiol-polyethylene glycol-epoxy aqueous solution have a strong interaction with silver, thereby stabilizing the nanosilver particles and preventing them from agglomerating, forming a uniform nanosilver / thiol-polyethylene glycol-epoxy composite solution.

[0025] A2: Add amino carbon nanotubes to 1 g / L nanosilver / thiol-polyethylene glycol-epoxy composite solution, react at 40°C for 30-50 min, filter and dry to obtain a carbon source.

[0026] The dosage ratio of the nanosilver / thiol-polyethylene glycol-epoxy composite solution to the amino-modified carbon nanotubes is 200-250 mL:0.4 g.

[0027] The epoxy groups of the nanosilver / thiol-polyethylene glycol-epoxy composite solution can react with the amino groups on the surfaces of the amino-modified carbon nanotubes to generate hydroxyl groups, and a carbon source is obtained after drying.

[0028] Beneficial effects of the present invention:

[0029] 1. The present invention uses the substance obtained by reacting the nanosilver / thiol-polyethylene glycol-epoxy composite solution with amino carbon nanotubes as a carbon source to carbon-wrap the lithium manganese iron phosphate material. The carbon nanotubes and nanosilver in the carbon source have good electrical conductivity. When it is coated on the surface of lithium iron phosphate or other positive electrode material particles, a conductive carbon coating can be formed. This carbon coating can serve as a channel for electron conduction, significantly improving the electrical conductivity of the material.

[0030] 2. The epoxy group of the nanosilver / thiol-polyethylene glycol-epoxy composite solution can react with the amino group on the surface of the amino carbon nanotubes to generate hydroxyl groups. The hydroxyl groups and polyethylene glycol can improve the hydrophilicity of the carbon source, thereby increasing the dispersibility of the carbon source in water. This improvement in hydrophilicity is conducive to the interaction between the carbon source and the aqueous lithium manganese iron phosphate substrate, thereby promoting the formation of a more uniform coating layer, which is conducive to building a uniform conductive network and improving the conductivity of the material. The optimization of the conductive network can also promote the diffusion and embedding / de-embedding process of lithium ions, allowing more active substances to participate in the electrochemical reaction, thereby increasing the gram capacity of the material.

[0031] 3. The polyethylene glycol after high-temperature cracking forms a porous carbon layer, which is evenly coated around the lithium manganese iron phosphate substrate to improve its conductivity. The polyethylene glycol after high-temperature sintering can be used as a binder, so that the carbon source forms a dense conductive network and improves the conductive properties of the material.

[0032] 4. The dense conductive network provides a good channel for electron migration, reduces the internal resistance of the battery and the charge and discharge polarization, thereby improving the electrochemical activity and utilization rate of the positive electrode material. At the same time, carbon coating can also effectively inhibit the agglomeration and growth of positive electrode material particles, maintain the nanostructure of the particles, and reduce the diffusion distance of lithium ions inside the active particles. All of these help to improve the cycle stability and life of the positive electrode material.

[0033] 5. The present invention is conducive to the preparation of lithium iron manganese phosphate positive electrode materials with the best comprehensive performance by accurately controlling the addition amount of carbon source. When the amount of carbon source added is too much, the carbon particles will agglomerate together, resulting in an increase in the size of the lithium iron manganese phosphate particles, which will reduce the specific surface area of ​​the active material, thereby reducing the contact area between the active material and the electrolyte, affecting the diffusion and insertion / deinsertion process of lithium ions, and ultimately leading to a decrease in gram capacity; when the carbon source is insufficient, the contact resistance between the lithium iron manganese phosphate particles increases, and the diffusion path of lithium ions is restricted, which will significantly reduce the conductivity of the positive electrode material. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] The amino carbon nanotubes of the present invention were purchased from Xianfeng Nanomaterial Technology Co., Ltd., with the serial number XFM62, a length of 50 μm, a diameter of 8-15 nm, a purity of >97.0 wt%, an amino content of >0.45 wt%, and a type of multi-walled carbon nanotubes;

[0036] Thiol-polyethylene glycol-epoxy was purchased from Xi'an Kaixin Biotechnology Co., Ltd. with a molecular weight of 0.6K.

[0037] Preparation Example 1

[0038] The preparation method of the carbon source in this preparation example is:

[0039] A1: 6 g of mercapto-polyethylene glycol-epoxy was mixed with 150 mL of DMF to obtain a mixed solution A, 5 mL of 0.06 mol / L mixed solution A, 5 mL of 0.01 mol / L silver nitrate aqueous solution, and 1 mL of 0.5 mol / L sodium borohydride aqueous solution were stirred evenly, and reacted at room temperature for 30 min to obtain a nanosilver / mercapto-polyethylene glycol-epoxy composite solution.

[0040] A2: Add 0.4 g of amino carbon nanotubes to 200 mL of 1 g / L nanosilver / thiol-polyethylene glycol-epoxy composite solution, react at 40° C. for 30 min, filter and dry to obtain a carbon source.

[0041] Preparation Example 2

[0042] The preparation method of the carbon source in this preparation example is:

[0043] A1: 6 g of mercapto-polyethylene glycol-epoxy was mixed with 125 mL of DMF to obtain a mixed solution A, 5 mL of 0.06 mol / L mixed solution A, 5 mL of 0.01 mol / L silver nitrate aqueous solution, and 1 mL of 0.5 mol / L sodium borohydride aqueous solution were stirred evenly, and reacted at room temperature for 35 min to obtain a nanosilver / mercapto-polyethylene glycol-epoxy composite solution.

[0044] A2: Add 0.4 g of amino carbon nanotubes to 225 mL of 1 g / L nanosilver / thiol-polyethylene glycol-epoxy composite solution, react at 40° C. for 40 min, filter and dry to obtain a carbon source.

[0045] Preparation Example 3

[0046] The preparation method of the carbon source in this preparation example is:

[0047] A1: 6 g of mercapto-polyethylene glycol-epoxy was mixed with 100 mL of DMF to obtain a mixed solution A, 5 mL of 0.06 mol / L mixed solution A, 5 mL of 0.01 mol / L silver nitrate aqueous solution, and 1 mL of 0.5 mol / L sodium borohydride aqueous solution were stirred evenly, and reacted at room temperature for 40 min to obtain a nanosilver / mercapto-polyethylene glycol-epoxy composite solution.

[0048] A2: Add 0.4 g of amino carbon nanotubes to 250 mL of 1 g / L nanosilver / thiol-polyethylene glycol-epoxy composite solution, react at 40° C. for 50 min, filter and dry to obtain a carbon source.

[0049] Preparation Example 4

[0050] The preparation method of the carbon source in this preparation example is different from that in Preparation Example 1, the "thiol-polyethylene glycol-epoxy" in Step A1 of Preparation Example 1 is replaced by "methoxy-polyethylene glycol-epoxy (molecular weight 0.6K)", and the remaining raw materials, processes and parameters are the same as those in Preparation Example 1.

[0051] Preparation Example 5

[0052] The preparation method of the carbon source in this preparation example is different from that in Preparation Example 1, the "thiol-polyethylene glycol-epoxy" in Step A1 of Preparation Example 1 is replaced by "methoxy-polyethylene glycol-thiol (molecular weight 0.6K)", and the remaining raw materials, processes and parameters are the same as those in Preparation Example 1.

[0053] Preparation Example 6

[0054] The preparation method of the carbon source in this preparation example is:

[0055] A1: Mix 5 mL of 0.01 mol / L silver nitrate aqueous solution and 1 mL of 0.5 mol / L sodium borohydride aqueous solution and react at room temperature for 30 min to obtain a nanosilver solution.

[0056] A2: Add 0.4 g of amino carbon nanotubes to 200 mL of 1 g / L nanosilver solution, react at 40° C. for 30 min, filter, and dry to obtain a carbon source.

[0057] Preparation Example 7

[0058] In this preparation example, the carbon source is 0.4 g of amino-modified carbon nanotubes.

[0059] Example 1

[0060] This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, comprising the following steps:

[0061] S1: Dissolve 9.7 g of ferric nitrate, 10.7 g of manganese nitrate and 1.9 g of citric acid in 100 mL of deionized water, adjust the pH value of the mixed solution to 2-4, and heat and stir for 2 h to obtain a dry gel;

[0062] S2: The dry gel was calcined in a muffle furnace at 200°C for 1 min, then taken out, cooled, and ground to obtain powder A;

[0063] S3: Powder A was calcined at 400°C for 1 h under a nitrogen atmosphere, and then ground to obtain powder B;

[0064] S4: Mix all the powder B, 7.6g lithium carbonate, 11.5g ammonium dihydrogen phosphate, 1g carbon source prepared in Preparation Example 1 (accounting for 4% of the total mass of all raw materials except water) and 70mL deionized water, and then sand grind them. The sand grinding particle size D50 is ≤250nm. After sand grinding, the slurry is spray dried to obtain powder C.

[0065] S5: calcine powder C at 600° C. for 8 h in an ammonia atmosphere, and then crush and sieve to obtain lithium manganese iron phosphate positive material. The particle size after crushing is D50≤1.3 μm.

[0066] Example 2

[0067] This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, comprising the following steps:

[0068] S1: 8 g of ferric sulfate, 10.7 g of manganese nitrate and 9.6 g of citric acid were dissolved in 100 mL of deionized water, the pH value of the mixed solution was adjusted to 2-4, and heated and stirred for 4 h to obtain a dry gel;

[0069] S2: The dry gel was calcined in a muffle furnace at 300°C for 5 min, then taken out, cooled, and ground to obtain powder A;

[0070] S3: Powder A was calcined at 450°C for 1.5 h under a nitrogen atmosphere, and then ground to obtain powder B;

[0071] S4: Mix all the powder B, 7.6g lithium carbonate, 11.5g ammonium dihydrogen phosphate, 1.6g carbon source prepared in Preparation Example 2 (accounting for 6% of the total mass of all raw materials except water) and 70mL deionized water, and then sand grind them. The sand grinding particle size D50 is ≤250nm. After sand grinding, the slurry is spray dried to obtain powder C.

[0072] S5: calcine powder C at 700° C. for 9 h in an ammonia atmosphere, and then crush and sieve to obtain lithium manganese iron phosphate positive material. The particle size after crushing is D50≤1.3 μm.

[0073] Example 3

[0074] This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, comprising the following steps:

[0075] S1: Dissolve 7.6 g of ferric acetate, 10.7 g of manganese nitrate and 9.6 g of citric acid in 100 mL of deionized water, adjust the pH value of the mixed solution to 2-4, and heat and stir for 6 h to obtain a dry gel;

[0076] S2: The dry gel was calcined in a muffle furnace at 400°C for 10 min, then taken out, cooled, and ground to obtain powder A;

[0077] S3: Powder A was calcined at 500°C for 2 h under a nitrogen atmosphere, and then ground to obtain powder B;

[0078] S4: Mix all the powder B, 7.6g lithium carbonate, 11.5g ammonium dihydrogen phosphate, 2.1g carbon source prepared in Preparation Example 3 (accounting for 8% of the total mass of all raw materials except water) and 70mL deionized water, and then sand grind them. The sand grinding particle size D50 is ≤250nm. After sand grinding, the slurry is spray dried to obtain powder C.

[0079] S5: calcine powder C at 800° C. for 10 h in an ammonia atmosphere, and then crush and sieve to obtain lithium manganese iron phosphate positive material. The particle size after crushing is D50≤1.3 μm.

[0080] Comparative Example 1

[0081] A method for preparing a lithium manganese iron phosphate positive electrode material, compared with Example 1, the difference is that the carbon source in Example 1 is replaced by the product prepared in Preparation Example 4, and the other raw materials, processes and parameters are the same as Example 1.

[0082] Comparative Example 2

[0083] A method for preparing a lithium manganese iron phosphate positive electrode material, compared with Example 1, the difference is that the carbon source in Example 1 is replaced by the product prepared in Preparation Example 5, and the remaining raw materials, processes and parameters are the same as Example 1.

[0084] Comparative Example 3

[0085] A method for preparing a lithium manganese iron phosphate positive electrode material, compared with Example 1, the difference is that the carbon source in Example 1 is replaced by the product prepared in Preparation Example 6, and the other raw materials, processes and parameters are the same as Example 1.

[0086] Comparative Example 4

[0087] A method for preparing a lithium manganese iron phosphate positive electrode material, compared with Example 1, the difference is that the carbon source in Example 1 is replaced by the product prepared in Preparation Example 7, and the other raw materials, processes and parameters are the same as Example 1.

[0088] Comparative Example 5

[0089] A method for preparing a lithium manganese iron phosphate positive electrode material, compared with Example 1, the difference is that the "1g of carbon source prepared in Preparation Example 1 (accounting for 4% of the total mass of all raw materials excluding water)" in Example 1 is replaced by "0.8g of carbon source prepared in Preparation Example 1 (accounting for 3% of the total mass of all raw materials excluding water).

[0090] Comparative Example 6

[0091] A method for preparing a lithium manganese iron phosphate positive electrode material, compared with Example 3, the difference is that the "2.1g of the carbon source prepared in Preparation Example 3 (accounting for 8% of the total mass of all raw materials excluding water)" in Example 3 is replaced by "2.4g of the carbon source prepared in Preparation Example 1 (accounting for 9% of the total mass of all raw materials excluding water).

[0092] The performance of the lithium iron manganese phosphate positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 6 was tested, and the results are shown in Table 1:

[0093] 1. Comprehensive performance test of positive electrode materials: The positive electrode materials and carbon black prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were added to PVDF glue to obtain positive electrode slurry. The mass ratio of positive electrode material, carbon black and PVDF glue was 90:5:5. The positive electrode slurry was coated on the surface of the positive electrode collector, and the positive electrode sheet was prepared after roller drying. The positive electrode sheet and the graphite negative electrode sheet were assembled into a full battery for verification, and the cycle, rate and gram capacity were tested. The cycle performance was tested at 25°C (1C / 1C2.0-4.3V), and the gram capacity was tested at 0.1C (25°C2.0-4.3V).

[0094] 2. Material powder resistance detection: Add the positive electrode material to the sample container, put it into the powder resistivity tester, pressurize it and keep it stable, connect the current clamp and voltage clamp, read the resistivity value, read it twice in the positive and negative directions and take the average value.

[0095] Table 1

[0096]

[0097] It can be seen from Table 1 that the lithium iron manganese phosphate positive electrode materials prepared in Examples 1-3 have excellent electrochemical properties. Among them, Comparative Example 1 does not contain a mercapto group, so it cannot have a strong interaction with silver, stabilize the nanosilver particles and prevent them from agglomerating, and form a uniform nanosilver / mercapto-polyethylene glycol-epoxy composite solution, which reduces the conductivity and comprehensive performance of the positive electrode material; Comparative Example 2 does not contain an epoxy group, and cannot combine with the amino carbon nanotubes to form a hydroxyl group, thereby reducing the dispersion of the carbon source between the aqueous lithium iron manganese phosphate substrates, and cannot form a uniform coating layer, which is not conducive to building a uniform conductive network, and reduces the conductivity and discharge capacity and other properties; Comparative Example 2 does not contain a mercapto group, an epoxy group and polyethylene glycol, and the carbon source has poor dispersion, cannot form a uniform coating layer, which is not conducive to building a uniform conductive network, The conductivity, discharge capacity and other properties are reduced; Comparative Example 4 contains only amino carbon nanotubes, and the conductivity, discharge capacity and other properties are the worst; when the carbon source is insufficient in Comparative Example 5, the contact resistance between the lithium iron manganese phosphate particles increases, and the diffusion path of lithium ions is restricted, which will reduce the rate performance of the battery, that is, the capacity and performance of the battery will be significantly reduced under high-rate charge and discharge conditions; when the amount of carbon source added in Comparative Example 6 is too much, the carbon particles will agglomerate together, resulting in an increase in the size of the lithium iron manganese phosphate particles, which will reduce the specific surface area of ​​the active material, thereby reducing the contact area between the active material and the electrolyte, affecting the diffusion and insertion / deinsertion process of lithium ions, and ultimately leading to a decrease in gram capacity.

[0098] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0099] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a lithium manganese iron phosphate positive electrode material, characterized in that: The following steps are involved: S1: dissolving a soluble iron source, a soluble manganese source and a complexing agent in 100 mL of deionized water, adjusting the pH value of the mixed solution to 2-4, and heating and stirring for 2-6 hours to obtain a dry gel; S2: taking out the dry gel after calcination, cooling and grinding to obtain powder A; S3: calcining and grinding powder A under a nitrogen atmosphere to obtain powder B; S4: powder B, a lithium source, a phosphorus source, a carbon source and 70 mL of deionized water are uniformly mixed and sand-milled, and spray-dried to obtain powder C, wherein the carbon source is obtained by drying after the reaction of a nanosilver / thiol-polyethylene glycol-epoxy composite solution with amino carbon nanotubes; S5: calcining powder C in a nitrogen atmosphere, crushing and sieving to obtain lithium manganese iron phosphate positive electrode material.

2. The method for preparing a lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step S1, the molar ratio of the soluble iron source, the soluble manganese source and the complexing agent is x:y:(0.1-1.0), x+y=1, respectively, in terms of Fe and Mn; the soluble iron source is one or more of ferrous sulfate, ferrous nitrate, ferrous acetate, ferric sulfate, ferric nitrate and ferric acetate; the soluble manganese source is one or more of manganous sulfate, manganous nitrate and manganous acetate; and the complexing agent is one or more of citric acid, ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, sodium gluconate and sodium alginate.

3. The method for preparing a lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step S2, the calcination temperature is 200-400° C., and the calcination time is 1-10 min.

4. The method for preparing a lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step S3, the calcination temperature is 400-500° C., and the calcination time is 1-2 hours.

5. The method for preparing a lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step S4, the molar ratio of powder B, lithium source and phosphorus source calculated as Fe+Mn, Li and P respectively is 1:1:1; the sand grinding particle size D50≤250nm; the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium nitrate and lithium acetate; the phosphorus source is one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate and disodium hydrogen phosphate.

6. The method for preparing a lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step S4, the mass of the carbon source accounts for 4-8% of the total mass of all raw materials except water.

7. The method for preparing a lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step S5, the calcination temperature is 600-800°C, and the calcination time is 8-10 hours; the particle size D50 after crushing is ≤1.3 μm.

8. The method for preparing a lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The steps for preparing the carbon source are as follows: A1: Mix thiol-polyethylene glycol-epoxy with DMF to obtain a mixed solution A, and evenly stir 0.06 mol / L of the mixed solution A, 0.01 mol / L silver nitrate aqueous solution, and 0.5 mol / L sodium borohydride aqueous solution, and react at room temperature for 30-40 min to obtain a nanosilver / thiol-polyethylene glycol-epoxy composite solution; A2: Add amino carbon nanotubes to 1 g / L nanosilver / thiol-polyethylene glycol-epoxy composite solution, react at 40°C for 30-50 min, filter and dry to obtain a carbon source.

9. The method for preparing a lithium iron manganese phosphate positive electrode material according to claim 8, characterized in that: In step A1, the volume ratio of mixed solution A, silver nitrate aqueous solution and sodium borohydride aqueous solution is 5:5:1; the amount ratio of mercapto-polyethylene glycol-epoxy to DMF in mixed solution A is 6g:100-150mL; in step A2, the amount ratio of nanosilver / mercapto-polyethylene glycol-epoxy composite solution to amino carbon nanotubes is 200-250mL:0.4g.

10. A lithium manganese iron phosphate positive electrode material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Carbon-coated lithium manganese iron phosphate composite material and preparation method thereof

    CN114620703A